ANALYSIS OF EMPLOYEE INVOLVEMENT IN ONLINE OJEK DRIVERS IN BATAM CITY - Antony Sentoso; Yuli Indah Fajar Dini (Journal of Business Studies and Management Review, 2020)
The number of internet users in Indonesia has already reached 64% from the total of Indonesia citizens which is more than 175.4 millions. And in April 2020, the total number of ojek online drivers in Indonesia is estimated to be 4 million drivers. It becomes interesting to make a study about employee engagement on ojek online drivers because of their partnership relation with online transportation company which owns the application. Because ojek online drivers are also free to decide their own operational hours and they can join more than one application, Respondents taken for employee engagement study were obtained through random sampling conducted to ojek online drivers who operated in Batam City. The writer distributed hard copy of 300 questionnaires straight to the drivers who operate in the fields and also distributed the questionnaires by online using Google Form through whatsapp application. After doing the verification and outlier test to 417 respondent data, only 351 data were left for further analysis by using SPSS (Statistical Package for Social Science) version 24. The result of the research described that reward and recognition, employee empowerment and leadership significantly have positive influence to the employee engagement of ojek online drivers to the owner of online transportation application.